ChemInform Abstract: Two Members of the X4Nb16O56 Family (X: Ge, Si) Based on [(GeOH)2Ge2Nb16H2O54] 12‐ and [K(GeOH)2Ge2Nb16H3O54 ]10‐. Issue 48 (26th November 2013) - Zhang, Xin; Liu, Shu‐Xia; Li, Shu‐Jun; Gao, Yu‐Huan; Wang, Xue‐Na; Tang, Qun; Liu, Yi‐Wei
Abstract (III) and (VI) are characterized by single crystal XRD, IR and UV/VIS diffuse reflectance spectroscopy, and electrochemical measurements.